Land : [compact disc, unabridged] a novel - O'Farrell, Maggie, 1972- (Penguin Random House, 2026)
On a windswept peninsula stretching out into the Atlantic, Tomás and his reluctant son, Liam, are working for the great Ordnance Survey project to map the whole of Ireland. The year is 1865, and in a country not long since ravaged and emptied by the Great Hunger, the task is not an easy one. Tomás, however, is determined that his maps will be a record of the disaster.